Chemical Constituents from Fruit of Melia azedarach L. in Vietnam - Vu, Thi Hien; Nguyen, Ngoc Tuan; Hoang, Van Luu; Vu, Dinh Hoang (Old Journal, 2019)
Two flavonoids (apigenin and quercetin 3-O-[α-L-rhamnopyranosyl-(1→6)-β-D-glucopyranoside]), a coumarin (scopoletin), a phenolic (vanillic acid), a triterpenoid (taraxerol) and two steroids (β-sitosterol and β-sitosterol-3-O-β-D-glucopyranoside) were isolated from the methanolic extract of the fruits of Melia azedarach L., using silica gel column chromatography methods. The structures of these compounds were elucidated using a combination of UV, IR, 1D and 2D NMR techniques (¹H-, ¹³C-NMR, COSY, HSQC and HMBC), MS analyses, and the comparison with the literature data. This is the first isolation of the compounds from Melia azedarach growing in Vietnam.